Tolerability of high-dose ceftriaxone in CNS infections: a prospective multicentre cohort study. (29th January 2019) - Le Turnier, Paul; Navas, Dominique; Garot, Denis; Guimard, Thomas; Bernard, Louis; Tattevin, Pierre; Vandamme, Yves Marie; Hoff, Jérôme; Chiffoleau, Anne; Dary, Martin; Leclair-Visonneau, Laurene; Grégoire, Matthieu; et al.
Abstract: Background: Ceftriaxone is widely used to treat community-acquired CNS bacterial infections. French guidelines for meningitis in adults promote 75–100 mg/kg/day ceftriaxone without an upper limit for dosage, yet little is known about the pharmacology and tolerability of such regimens. Patients and methods: A multicentre prospective cohort study was conducted in adult patients to assess the adverse drug reactions (ADRs) of high-dose ceftriaxone (i.e. daily dosage ≥4 g or ≥75 mg/kg) in CNS infections and to analyse their related factors. Drug causality was systematically assessed by an expert committee who reviewed the medical charts of all included patients. Results: A total of 196 patients were enrolled over a 31 month period. Median dosage and duration of ceftriaxone were 96.4 mg/kg/day (7 g/day) and 8 days, respectively. Nineteen ceftriaxone-related ADRs (mainly neurological) occurred in 17 patients (8.7%), with only one case of treatment discontinuation (biliary pseudolithiasis). In univariate analysis, older age, male gender, renal impairment and high trough ceftriaxone plasma concentration were associated with ceftriaxone-related ADRs. Conclusions: High-dose ceftriaxone for CNS infection administered as recommended by French guidelines in adults was well tolerated overall, suggesting these recommendations could be applied and generalized. In patients with advanced age or renal insufficiency, prescription should be done with caution and therapeutic drug monitoring could be useful.